2010
DOI: 10.1111/j.1556-4029.2010.01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Age Estimation on Digital X‐ray Images: Medial Epiphyses of the Clavicle and First Rib Ossification in Relation to Chronological Age*,†

Abstract: In recent years, there has been a renewed interest in forensic sciences about forensic age estimation in living subjects by means of radiological methods. This research was conducted on digital thorax X-rays to test the usefulness of some radiological changes in the clavicle and first rib. The sample consisted in a total of 123 subjects of Spanish origin (61 men and 62 women; age range: 5-75 years). From all subjects, a thorax posterior-anterior radiograph was obtained in digital format. Scoring for fusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 26 publications
3
41
1
3
Order By: Relevance
“…A wide variety of methods based on the skeletal maturity [40][41][42][43][44] and dental development 31,45,46 have been published for age estimation. All these methods have proven to be accurate when applied to the individuals from the population from which those standards are derived 47 .…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of methods based on the skeletal maturity [40][41][42][43][44] and dental development 31,45,46 have been published for age estimation. All these methods have proven to be accurate when applied to the individuals from the population from which those standards are derived 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In this process, respiratory stress seems to be the main cause of ossification of the first rib, whereas it is chest expansion in the lower ribs. 13 In our study, mean ages for calcification were 5 Garamendi et al reported stage 0 calcification predominantly in subjects between 5 and 19 years of age and stage 3 and 3 calcification in 24 years old subjects. 12,13 In our study, stage 0 calcification was present in subjects between 1 and 14 years of age and we had results similar to those of Garamendi et al for stage 2 and 3 subjects.…”
Section: Discussionmentioning
confidence: 79%
“…While the median value for stage 0 was 5.00 years in our study, it was 17.64 years in their study. 12,13 Our study group included a higher number of pediatric subjects compared to their study and there was a difference in mean ages of stage 0 groups of the two studies due to median values. Overall Spearman's rho value was 0.904 for the study group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations